1927 Mich. Pub. Acts 891, No.372, § 9 - (:unkn) unknown (My University, 1927)
An Act to Regulate and License the Selling, Purchasing, Possessing and Carrying of Certain Firearms, § 9: Required registration for the owners of pistols
Keywords: REGISTRATION